2018
DOI: 10.1007/s00203-018-1507-1
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids from Phyllocaulis boraceiensis mucus block the replication of influenza virus

Abstract: Influenza viruses cause worldwide outbreaks and pandemics in humans and animals every year with considerable morbidity and mortality. The molecular diversity of secondary metabolites extracted from mollusks is a good alternative for the discovery of novel bioactive compounds with unique structures and diverse biological activities. Phyllocaulis boraceiensis is a hermaphroditic slug that exudes mucus, in which was detected hydroxy polyunsaturated fatty acids that exhibited potent antiviral activity against meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Fatty acids are ubiquitous in nature and have shown many biological activities, such as antimicrobial [19], antifungal [20], antiviral [21], nematicidal [22] or anticancer activities [23]. Recently, linoleic acid has also been identified as essential for the sexual cycle of the pathogen Toxoplasma gondii in the feline gut [24] or the induction of a memory response of increased pathogenicity of Pseudomonas aeruginosa during its passage through the host [25].…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids are ubiquitous in nature and have shown many biological activities, such as antimicrobial [19], antifungal [20], antiviral [21], nematicidal [22] or anticancer activities [23]. Recently, linoleic acid has also been identified as essential for the sexual cycle of the pathogen Toxoplasma gondii in the feline gut [24] or the induction of a memory response of increased pathogenicity of Pseudomonas aeruginosa during its passage through the host [25].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 2-hydroxydecanoic acid has shown to inhibit the replication of varicella-zoster virus, poliovirus and HIV-1 [42] . Recently, hydroxy polyunsaturated fatty acids have also shown antiviral activity against measles influenza virus [43] . In line with this, we also found a strong association between the expression of ACE2 in peripheral leukocytes and the circulating levels of 19,20-dihydroxydocosapentaenoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, biomedical research efforts have been focused in Europe (34%), North America (28%), and Asia (China and India, 27%). Only one South American species has been studied [153,154] and Australian species are also underrepresented (Table S1). Numerous sources attest to the importance of molluscs as traditional food sources as opposed to traditional medicines in Australia and throughout the Indo-pacific [155,156].…”
Section: Taxonomic and Geographic Trendsmentioning
confidence: 99%
“…Preliminary antibacterial results from disc diffusion assays using some respiratory pathogens are presented by Cilia and Fratini [189], but statistically meaningful data are yet to be derived. de Toledo-Piza et al (2016) demonstrated impressive anti-viral activity with concentrated mucus from the terrestrial shell-less mollusc Phyllocaulis boraceiensis whereby host cell pre-treatment reduced Influenza A (H1N1) and measles virus-induced cytopathic effects by up to 80% with no host cell cytotoxicity [153,154]. Further studies should incorporate bioassay guided fractionation of concentrated mucus extracts to isolate and identify the active factors.…”
Section: Antimicrobial Activitymentioning
confidence: 99%